PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN AKTIVITAS BELAJAR MATERI POLIMER SISWA KELAS XII IPA SMAN 2 PONTIANAK - Danggus, Grardus (Universitas Tanjungpura, 2015)
This research has been conducted to figure out the improvement of the students learning activities in polymer lesson at twelft grade of science program in SMAN 2 Pontianak by the application of cooperative learning model type numbered heads together. The form of this research is Classroom Action Research. The research was conducted in three cycles. The students learn about the meaning and the reaction how the polymer is formed, the classification of polymer, kinds of plastic, the use and the impact of polymer as well. The instrument used is observation of the studentsâ€™ activities and questioners. Based on the data analysis, it can be concluded that there is improvement on the students learning activities. The percentage of the students activities is 29,03% in the first cycle, 43,75% in the second cycle and 84,38% in the third cycle. It is recommended for the teachers to choose cooperative learning model type numbered heads together to become one of the learning model alternative in polymer lesson to improve Â the studentsâ€™ learning activities. Keywords : Cooperative learning, numbered heads together.